One stage transanal full thickness pull-through operation for rectosigmoid Hirschsprung’s disease - Hossain, A. K. M. Zahid; Hasan, Gazi Zahirul; Mandal, Susankar Kumar; Nooruzzaman, Md.; Shahinoor, A.; Koirala, Dinesh Prasad (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
The surgical management of Hirschsprung's disease (HD) has changed from the original staged operations to the latest introduced minimally invasive one stage techniques. One stage transanal full thickness Swenson-like procedure is a new concept of single stage procedure for HD. We reviewed the early outcome of one stage transanal Swenson-like pull-through operation for rectosigmoid HD. By using the transanal concept we choose to apply Swenson's principle in transanal dissection for the primary treatment of HD and describe technical aspects and impact on fecal and urinary function. We reviewed our series of HD patient who underwent one-stage transanal full thickness, Swenson-like rectosigmoid dissection, assessing for postoperative stricture or stenosis, anastomotic leak, enterocolitis, obstruction and long-term results for bowel and urinary function. Of 15 patients all had the transanal resection, the age of the patients ranged from 6 months to 5 years. The average length of resection was 20 ± 5 cm. Mean follow-up was 24 months. 10 patients were at least three years old at follow-up and were assessed for urinary and fecal continence. All had the voluntary bowel movement and urinary continence. Three patients had episodes of postoperative enterocolitis and two patients developed stenosis at the anastomotic site. Postoperative frequent bowel movement was present in all patients and continued for 2-8 weeks. In conclusion, our data support the fact that a modification of Swenson's original transabdominal dissection concept using the recently describe transanal approach is an excellent technique for HD and produces excellent long-term outcome for fecal and urinary function.